Kemampuan Problem Solving pada Mahasiswa Tingkat Akhir: Bagaimana Peranan Critical Thinking - Mohammad Rizki Annabil; Niken Titi Pratitis; Isrida Yul Arifiana (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Final year students face a variety of challenges ranging from academic challenges, psychological and emotional challenges, and self-management challenges. Problem solving ability is important for final year students to solve all these challenges. In order for problem solving ability to be effective, critical thinking is needed which is an important factor in problem solving. This study aims to determine the relationship between critical thinking and problem solving ability in final year students. This type of research is quantitative correlation. The population of this study were final year students of Universitas 17 Agustus 1945 Surabaya totaling 2338 consisting of students from generation 2018 to 2022. The research sample was determined through the Krejcie table with a total of 201 students. The sampling method used Snowball sampling with Spearman Rank Correlation data analysis technique. The results show a positive correlation between critical thinking and problem-solving Ability. Keywords: Critical Thinking; Problem Solving Ability, Final year students. Abstrak Mahasiswa tingkat akhir berbagai macam tantangan mulai dari tantangan akademis, tantangan psikologis dan emosional, dan tantangan manajemen diri. Kemampuan problem solving menjadi penting bagi mahasiswa tingkat akhir untuk menyelesakain semua tantangan tersebut. Agar kemampuan problem solving menjadi efektif diperlukan critical thinking yang faktor penting dalam penyelesaian masalah. Penelitian ini bertujuan untuk mengetahui hubungan antara critical thinking dengan kemampuan problem solving pada mahasiswa tingkat akhir. Jenis penelitian ini adalah kuantitatif korelasional. Populasi dalam penelitian ini adalah mahasiswa tingkat akhir Universitas 17 Agustus 1945 Surabaya berjumlah 2338 terdiri dari mahasiswa Angkatan 2018 hingga 2022. Sampel penelitian ditentukan melalui tabel krejcie dengan berjumlah 201 mahasiswa. Metode pengambilan sampel menggunakan Snowball sampling dengan teknik analisis data Spearman Rank Correlation. Hasil terdapat hubungan positif antara critical thinking dan kemampuan problem solving. Kata kunci: Critical Thinking; Kemampuan Problem solving; Mahasiswa Tingkat Akhir.